Childfree in Modern Muslim Communities of Lampung and West Java Provinces: A Maqāṣid al-sharī'ah Perspective - Mu'in, Fathul; Miswanto, Miswanto; Edy, Relit Nur; Santoso, Rudi; Fikri, Arif (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Recently, being childfree has become a trend in modern Muslim society. Childfree is practiced not only by celebrities but also by common people in Indonesia, particularly in Lampung and West Java provinces. On the one hand, the decision to be childfree is an individual right of each family, but it is considered contrary to the goals of Islamic law, which are to preserve offspring. This study examines the childfree phenomenon in modern Muslim communities in Lampung and West Java through the perspective of maqāṣid al-sharī'ah. This research employed a qualitative method with an ethnographic approach. The research suggested that modern Muslim communities in Lampung and West Java Provinces choose childfree for economic, mental, health, perspective, and environmental reasons. According to maqāṣid al-sharī'ah, being childfree contradicts Sharia's purpose of preserving offspring. Sharia promotes marriage and having healthy offspring. Meanwhile, Sharia cannot justify childfree due to lifestyle or economic factors. Specifically, a fear of not being able to provide for the child's future needs because Allah ensures livelihood for every servant who has faith and works diligently. At the same time, being child-free due to health reasons is permissible.